2020
DOI: 10.1136/bcr-2020-237678
|View full text |Cite
|
Sign up to set email alerts
|

Primary synovial sarcoma of the lung: a rare presentation, diagnostic dilemma and review of literature

Abstract: Primary synovial sarcoma of the lung (PSSL) is a rare tumour with only 0.5% incidence among other primary malignant lung tumours. Published medical literature regarding the natural history treatment protocol and clinical outcomes of PSSL remains limited. Here, we present a case of a 39-year-old man with primary synovial sarcoma with long-term follow-up, which was initially viewed as a metastasis from another unknown site. After evaluating histopathologically from the specimen post left lung metastasectomy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Patients mostly seek help due to cough, chest pain, difficulty in breathing, and hemoptysis. Although it resembles its soft tissue counterpart but is difficult to diagnose clinically and radiologically from other primary and metastatic lung tumors [7] . The diagnosis of primary pulmonary synovial sarcoma is based on clinical symptoms, radiological examination, pathology, and immunohistochemistry to exclude the possibility of another primary tumor and a metastatic sarcoma [10] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients mostly seek help due to cough, chest pain, difficulty in breathing, and hemoptysis. Although it resembles its soft tissue counterpart but is difficult to diagnose clinically and radiologically from other primary and metastatic lung tumors [7] . The diagnosis of primary pulmonary synovial sarcoma is based on clinical symptoms, radiological examination, pathology, and immunohistochemistry to exclude the possibility of another primary tumor and a metastatic sarcoma [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Primary pulmonary synovial sarcoma could occur in both genders equally [4] , [6] . In chest X-ray, synovial sarcoma often manifests as lung parenchyma mass with well-circumscribed rounded or lobulated borders [3] , [4] , [7] . Common computed tomography findings are solitary, large, well-circumscribed mass that enhances heterogeneously on contrast [2] , [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the world literature, it occurs only in 0.5% of cases of primary lung tumors. 1 At the same time, global statistics from 170,000 patients with primary malignant lung tumors (PMLTs) showed that approximately 50% of patients in the future would have lung metastases, which would be treatable. 2 In this case, data on the survival of patients after re‐resection of the lungs for lung metastases of synovial sarcoma show an average duration without disease recurrence of up to 25 months.…”
Section: Introductionmentioning
confidence: 99%
“…Synovial sarcoma of the lungs is an extremely rare pathology that is not commonly found in the daily clinical practice of thoracic and oncological surgeons. According to the world literature, it occurs only in 0.5% of cases of primary lung tumors 1 . At the same time, global statistics from 170,000 patients with primary malignant lung tumors (PMLTs) showed that approximately 50% of patients in the future would have lung metastases, which would be treatable 2 .…”
Section: Introductionmentioning
confidence: 99%